CONDITIONS FOR EFFICIENCY INCREASE INDEPENDENT WORK OF JUNIOR SCHOOLCHILDREN IN UKRAINIAN LANGUAGE LESSONS - Bilokonna, N.I. (Pedagogy of Higher and Secondary Education, 2006)
The article examines the essence of the independent learning on the Ukrainian language lessons in the primary school and defines the conditions to increase its efectiwness.